KELAYAKAN EKONOMI BAHAN BAKU INDUSTRI SEKUNDER DARI LIMBAH KAYU PEMBALAKAN DI PROPINSI JAMBI (The economic feasibility of utilizatiion of logging waste for secondary industry’s raw materials Jambi Province) - O K Karyono; hariyatno dwiprabowo (Jurnal Penelitian Hasil Hutan, 1993)
Raw material for the wood proccesing industries in Jambi Province, is supplied by the concessionaires in Jambi Province, as well as from other. regions such. as from Riau Province. As the number of wood industries increase raw material supply for wood industries in jambi need to be increased. To fill in part of the shortage, the uSe of logging waste needs to be encouraged.Of forest area of Jambi Province about 2,9 million ha, the amount of logging waste is estimaled around 162,118.51 cum. the amount of logging waste which have been used by some concessioners in the Jambi Province accounted for 3,83 percent This figure impliS. that logging waste utilization should be intensified, so raw material for secondary industries can be increased without necessarily to increase logging area, and it wil also save forest resurces and increase added value.Old study show that use of logging waste prpvides profit margin as much as : Rp. 6. 750,- per cubic meter for concessionaire,Rp.28.150,- for sawmill and Rp. 42.525.- for blackboard industries.